Pengembangan Modul IPA Berbasis Problem Solving Method Berdasarkan Karakteristik Siswa - Sunaji, Sunaji (JPB - Jurnal Pendidikan Biologi, 2022)
The development of the Science Module based on the Problem Solving Method is based on the background of analyzing the needs of students and teachers who really need references to science subjects according to their characteristics and needs. The purpose of this development is to develop a science learning module based on the problem solving method of Class IX semester I according to the needs and characteristics of students, especially from the aspect of learning objectives, learning implementation plans, module grids, and module evaluations. The development of this science learning module uses a questionnaire or questionnaire instrument. The object of this research is the IX grade students at SMPN 1 Bangilan Tuban. The results of data analysis are used to revise the development of learning modules for science subjects based on the probem solving method according to the trial design. To make it easier to make revision decisions, a qualifying level of feasibility assessment will be used with a scoring system and specified eligibility criteria. The results of this study indicate that the learning objectives, design, grid, and evaluation of learning are using the Problem Solving Method which has been revised by experts. designer, material expert, one-on-one trial that got a good score because it was on the right of the Likert scale with a median of 2.5. So it can be concluded that the integrated science module material for class IX semester 1 reflects the learning module through learning a good Problem Solving Method.